Residue, tillage and N-fertilizer rate affected yield and N efficiency in irrigated spring wheat. (5th December 2016) - Shah, Asad; Akmal, Mohammad; Khan, M. Jamal; Asim, Muhammad
ABSTRACT: Yield and nitrogen (N)-content in wheat was studied under applied treatments of crop residues (legume vs. cereal), tillage depths (deep vs. shallow) and N-fertilizer rates (0, 40, 80, 120 and 160 kg ha −1 ) at wheat-maize cropping systems. Experiments were conducted at Agronomy Research farm, the University of Agriculture, Peshawar Pakistan, during winter season 2009–2010 and 2010–2011 crop growth seasons. Well-chopped crop residues (5 t ha −1 ) on dry matter basis of legume ( Vigna unguicuata ) and cereal ( Zea mays ) were applied to soil and subsequently plowed with mold-board plow as deep tillage (DT) and cultivator as shallow tillage (ST) treatment (main plot treatments). A month after residue and tillage application, seedbed was prepared and wheat was planted with drill in rows 25 cm apart in middle of November each year. Phosphorus and potassium were applied uniformly 80 and 40 kg ha −1, respectively during seedbed preparation. N-fertilizer rates were applied in two splits: half 15 days after sowing (DAS) and other half 45 DAS (sub-plot treatment). Uniform cultural practices were applied during crop growth and development. Legumes residues amendments showed better responses than cereal but lower than no-residue treatment for N-content in leaf blade before anthesis (LBA), after anthesis (LAA), straw N-content (SNC), grain N-content (GNC), grain N-uptake (GNU), crop N-removal (CNR), recovery efficiency of added nitrogen (REAN), N-use efficiency (NUE), grain N-uptake (GNU) and grain yield. Likewise, shallow tillage proved better than deep tillage system for LBA, LAA, SNC, GNC, GNU, CNR, REAN, NUE, GNU and grain yield. Increased N-fertilizer from control onwards showed significant (p > 0.05) increments in LBA, LAA, SNC, GNC, GNU, CNR, N-uptake and grain yield. Treatments interaction was also found significant (p > 0.05). Study suggested, regardless of the given treatments, GNU and grain yield were in strong positive linear relationship. Legume residue incorporated shallow out yielded GNU and NUE of spring wheat in wheat-maize cropping system. It is concluded that LR and ST with 120 kg N ha −1 ensures production of good wheat quantity and quality.